Viscosity-adjustable hydrogel material as well as preparation method and application thereof

By regulating the chemical composition and structure of hydrogel materials, the adhesive and non-adhesive controllable and anti-freeze moisturizing properties are achieved, and the problems of existing hydrogel materials are solved at low temperature dehydration and insufficient biocompatibility. It is suitable for biomedical and flexible electronics.

CN119325491APending Publication Date: 2025-01-17SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380044152.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-08
Filing Date
2023-09-22
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing hydrogel materials cannot achieve the control and coexistence of sticky and non-adhesive properties, and will freeze and dehydrate at low temperatures, which has poor biocompatibility, which limits its application in biomedical materials and flexible electronic devices. .

Method used

By selecting and controlling chemical components such as monomers, crosslinking agents, long-chain polymers, dopamine hydrochloride and clay, an interpenetrating network structure is formed to achieve adjustable stickiness and non-adhesion, and adding moisturizers to improve the anti-freeze and moisturizing properties. A viscous adjustable hydrogel material is produced.

Benefits of technology

It realizes the adhesive and non-adhesive compatibility and coexistence of hydrogel materials, has anti-freeze moisturizing, self-healing, biocompatibility and flexibility, and can maintain structural integrity under low temperature environments and maintain good at room temperature. Moisturizing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119325491A_ABST
    Figure CN119325491A_ABST
Patent Text Reader

Abstract

The invention provides a viscosity-adjustable hydrogel material as well as a preparation method and application thereof. The viscosity-adjustable hydrogel material is prepared from the following raw materials in parts by weight: 10 to 30 parts of monomers, 1 to 20 parts of cross-linking agents, 0.1 to 5 parts of long-chain macromolecules, 0.01 to 5 parts of dopamine hydrochloride, 0.01 to 5 parts of clay and 50 to 90 parts of water. According to the viscosity-adjustable hydrogel material provided by the invention, compatibility and regulation of two characteristics of surface viscosity and non-viscosity of the hydrogel material can be easily realized by selecting chemical components and regulating the dosage, and the viscosity-adjustable hydrogel material has anti-freezing moisture retention, self-healing performance, biocompatibility and flexibility and can be applied to biomedical materials or flexible electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of self-repairing materials, and specifically relates to a viscosity-adjustable hydrogel material and a preparation method and application thereof. Background Art

[0002] Hydrogel is a hydrophilic polymer with a three-dimensional network structure synthesized from natural or synthetic materials. Due to the presence of hydrophilic groups such as -NH2, -COOH, and -OH, the hydrogel network can form hydrogen bonds with water molecules, allowing the hydrogel to absorb and retain a large amount of water. Hydrogels are not only highly flexible, but also have a soft rubber consistency similar to living tissue, making them ideal substances or carriers for various applications. By modifying and optimizing the original properties of hydrogels or by compounding them to give them new excellent properties, such as good biocompatibility, degradability, and antibacterial and anti-inflammatory properties, and making their physical properties, chemical properties, and structures easy to regulate, major breakthroughs have been made in many aspects such as biomedical materials and flexible electronic devices, and they have attractive application prospects.

[0003] Hydrogel is a gel material formed by physical or chemical cross-linking. Different cross-linking methods and matrix materials can give hydrogels adjustable physical and chemical properties. The large amount of water filled in its three-dimensional network structure helps to maintain good affinity between the hydrogel and the organism. In the field of biomedical materials, when hydrogels are used in the human body, in addition to their own ability to promote wound healing and anti-inflammatory effects and to play a therapeutic role in diseases such as tumors, they can also be used as carriers of proteins, nucleic acids and small molecule drugs. As an intelligent drug delivery system, it can realize the controlled release process of substances in the human body, solve the problem of drugs being easily enzymatically or hydrolyzed, and thus improve the stability of drug delivery.

[0004] Polymers contain abundant active groups, providing sufficient molecular modification and transformation space to design and construct three-dimensional cross-linked networks, including mechanical properties that conform to human tissue, enhanced conductivity and sensitivity, self-adhesion, self-healing, and 3D printing, etc., which meet the multifunctional integration and device processing requirements of flexible sensing materials. Biocompatible hydrogels allow electronic devices to directly contact human skin and can even be safely implanted in the body for long-term use, with minimal inflammatory or immune response to host tissues. In flexible electronic devices, the intrinsic weight and flexibility of hydrogels can alleviate the discomfort caused by foreign devices for long-term wear or implantation in the human body, achieve continuous and persistent monitoring of healthcare sensing applications, and meet the basic requirements of the next generation of intelligent monitoring systems for continuous and long-term monitoring. At the same time, biodegradable and renewable natural materials can eventually return to nature after their service, avoiding the environmental problem of electronic waste accumulation caused by the large-scale application of flexible electronics.

[0005] As a new functional material, hydrogel has the characteristics of high water absorption and retention, biocompatibility, flexibility, etc. It can be endowed with specific properties through the selection of different materials and means of modification and compounding. Therefore, hydrogel and its derivatives have high research value and are increasingly widely used in various fields.

[0006] CN115286731A discloses an external light-cured medical hydrogel and a preparation method thereof, wherein the medical hydrogel is obtained by subjecting a pre-gel light-cured solution to ultraviolet light curing reaction. CN110240712A discloses a high-stretch, high-viscosity, self-healing double-network hydrogel for tissue adhesion and a preparation method and application thereof, wherein the above hydrogels are only viscous and cannot achieve adjustable and coexistent properties of stickiness and non-stickiness, and have poor biocompatibility.

[0007] In the prior art, hydrogel materials exist in only one state, sticky or non-sticky, which cannot be adjusted. The sticky and non-sticky properties of the same hydrogel material cannot be adjusted and coexist, which limits its application. Secondly, when used below 0°C, the hydrogel will freeze and cannot be restored after dehydration after thawing. At the same time, the biocompatibility of the hydrogel is poor. Therefore, it is an issue that cannot be ignored to develop a hydrogel material with adjustable and coexistent sticky and non-sticky properties, antifreeze and moisture retention, self-healing, biocompatibility and elasticity, which is suitable for biomedical materials and flexible electronic devices. Summary of the invention

[0008] The present application provides a viscosity-adjustable hydrogel material, a preparation method and application thereof, which achieves the characteristics of adjustable and coexistent viscosity and non-viscosity by regulating with different chemical components, and at the same time has antifreeze and moisture retention, self-healing, biocompatibility and flexibility.

[0009] In a first aspect, the present application provides a viscosity adjustable hydrogel material, wherein the raw materials for preparing the viscosity adjustable hydrogel material include the following components in parts by weight: 10 to 30 parts by weight of monomer, 1 to 20 parts by weight of cross-linking agent, 0.1 to 5 parts by weight of long-chain polymer, 0.01 to 5 parts by weight of dopamine hydrochloride, 0.01 to 5 parts by weight of clay and 50 to 90 parts by weight of water.

[0010] The viscosity-adjustable hydrogel material provided in the present application is an interpenetrating network flexible elastic hydrogel material, which forms a gel through the reaction of monomers and cross-linking agents. The long-chain polymer can improve the overall flexibility and viscosity of the hydrogel material in the form of an interpenetrating network; dopamine hydrochloride can self-polymerize into polydopamine, which can also improve the overall viscosity of the hydrogel material and increase the self-healing performance in the form of an interpenetrating network; the strength of the hydrogel material can be improved by clay; through the selection of chemical components and the regulation of dosage, the viscosity-adjustable hydrogel material provided in the present application can achieve the regulation of sticky and non-sticky properties, that is, a sticky hydrogel material can be obtained, and a non-sticky hydrogel material can be obtained. A layer of non-sticky hydrogel material is covered on the surface of the sticky hydrogel material to obtain a hydrogel material with one side sticky and the other side non-sticky, which can achieve the compatibility and coexistence of sticky and non-sticky hydrogel materials.

[0011] In the preparation raw materials of the viscosity adjustable hydrogel material, the added amount of the monomer can be 10 to 30 parts by weight, for example, it can be 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, 22 parts by weight, 24 parts by weight, 26 parts by weight, 28 parts by weight or 30 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific points included in the range.

[0012] The amount of the cross-linking agent added can be 1 to 20 parts by weight, for example, 1 part by weight, 2 parts by weight, 4 parts by weight, 6 parts by weight, 8 parts by weight, 10 parts by weight, 12 parts by weight, 14 parts by weight, 16 parts by weight, 18 parts by weight or 20 parts by weight, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific points included in the range.

[0013] The addition amount of the long-chain polymer can be 0.1 to 5 parts by weight, for example, it can be 0.1 parts by weight, 0.5 parts by weight, 1 parts by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, 4.5 parts by weight or 5 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific points included in the range.

[0014] The added amount of dopamine hydrochloride can be 0.01 to 5 parts by weight, for example, it can be 0.01 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.5 parts by weight, 1 parts by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, 4.5 parts by weight or 5 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific points included in the range.

[0015] The added amount of the clay can be 0.01 to 5 parts by weight, for example, 0.01 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.5 parts by weight, 1 parts by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, 4.5 parts by weight or 5 parts by weight, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific points included in the range.

[0016] The amount of water added can be 50 to 90 parts by weight, for example, 50 parts by weight, 55 parts by weight, 60 parts by weight, 65 parts by weight, 70 parts by weight, 75 parts by weight, 80 parts by weight, 85 parts by weight or 90 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific points included in the range.

[0017] The following are preferred technical solutions of the present application, but are not intended to limit the technical solutions provided by the present application. Through the following preferred technical solutions, the objectives and beneficial effects of the present application can be better achieved and realized.

[0018] As a preferred technical solution, the monomer includes any one of acrylamide, methacrylamide or hydroxyethyl methacrylate, or a combination of at least two of them.

[0019] Preferably, the monomer comprises acrylamide.

[0020] As a preferred technical solution, the cross-linking agent includes polyethylene glycol diacrylate and / or N,N'-methylenebisacrylamide.

[0021] Preferably, the cross-linking agent comprises polyethylene glycol diacrylate.

[0022] Preferably, the number average molecular weight of the polyethylene glycol diacrylate is 600-1000.

[0023] As a preferred technical solution, the long-chain polymer includes polyethylene oxide and / or hydroxyethyl cellulose.

[0024] Preferably, the average molecular weight of the polyethylene oxide is 100,000 to 8,000,000, for example, 100,000, 500,000, 1,000,000, 1,500,000, 2,000,000, 2,500,000, 3,000,000, 3,500,000, 4,000,000, 5,000,000, 6,000,000, 7,000,000 or 8,000,000, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific values ​​included in the range.

[0025] Preferably, the viscosity of the hydroxyethyl cellulose is 100-6400 mPa.s, for example, it may be 100 mPa.s, 500 mPa.s, 1000 mPa.s, 1500 mPa.s, 2000 mPa.s, 3000 mPa.s, 4000 mPa.s, 5000 mPa.s, 6000 mPa.s or 6400 mPa.s, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific point values ​​included in the range.

[0026] As a preferred technical solution, the clay includes any one of lithium magnesium silicate, carbon fibers, silver nanoparticles, silicon dioxide nanoparticles or graphene oxide, or a combination of at least two thereof.

[0027] Preferably, the particle size of the silver nanoparticles is 10 to 100 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific point values ​​included in the range.

[0028] Preferably, the particle size of the silica nanoparticles is 10 to 500 nm, for example, it can be 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific point values ​​included in the range.

[0029] As a preferred technical solution, the raw materials for preparing the adjustable viscosity hydrogel material also include 10 to 50 parts by weight of a moisturizer, for example, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight or 50 parts by weight, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific points included in the range.

[0030] Preferably, the humectant includes polyols. The present application uses the humectant to impart antifreeze and moisturizing properties to the hydrogel material.

[0031] Preferably, the polyol comprises glycerol and / or ethylene glycol.

[0032] As a preferred technical solution, the raw materials for preparing the adjustable viscosity hydrogel material also include 0.2 to 2 parts by weight of an initiator, for example, 0.2 parts by weight, 0.4 parts by weight, 0.6 parts by weight, 0.8 parts by weight, 1 part by weight, 1.2 parts by weight, 1.4 parts by weight, 1.6 parts by weight, 1.8 parts by weight or 2 parts by weight, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific points included in the range.

[0033] Preferably, the initiator includes any one of a photoinitiator or a thermal initiator, and a photoinitiator is more preferred.

[0034] Preferably, the photoinitiator comprises 2-hydroxy-2-methyl-1-phenyl-1-propanone and / or 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide.

[0035] The viscosity-adjustable hydrogel material provided in the present application can initiate polymerization in different ways by selecting an initiator. For example, a photoinitiator can initiate polymerization by ultraviolet light irradiation, and a thermal initiator can initiate polymerization by heating.

[0036] In a second aspect, the present application provides a method for preparing the viscosity-adjustable hydrogel material as described in the first aspect, the preparation method comprising the following steps:

[0037] The monomer, the cross-linking agent, the long-chain polymer, the dopamine hydrochloride, the clay and the water are mixed to obtain the hydrogel solution precursor; the hydrogel solution precursor is reacted in the presence of the initiator to obtain the hydrogel material.

[0038] As a preferred technical solution, the mixed material also includes a moisturizer.

[0039] Preferably, the mixing temperature is 25-60°C, for example, it can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific point values ​​included in the range.

[0040] Preferably, the initiator is a photoinitiator, and the reaction is carried out under ultraviolet light.

[0041] Preferably, the reaction time is 1 to 5 min, for example, it can be 1 min, 1.5 min, 2 min, 2.5 min, 3 min, 3.5 min, 4 min or 5 min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific point values ​​included in the range.

[0042] Preferably, the reaction temperature is 18-35°C, for example, it can be 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 28°C, 30°C, 32°C, 34°C or 35°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific point values ​​included in the range.

[0043] As a preferred technical solution, the preparation method specifically comprises the following steps:

[0044] (1) mixing monomers, a cross-linking agent, a long-chain polymer, dopamine hydrochloride, a humectant, clay and water to obtain a hydrogel solution precursor;

[0045] (2) adding a photoinitiator to the hydrogel solution precursor obtained in step (1) to obtain a reaction system; and

[0046] (3) The reaction system obtained in step (2) is reacted under ultraviolet light to obtain the hydrogel material.

[0047] In a third aspect, the present application provides an application of the viscosity-adjustable hydrogel material as described in the first aspect in biomedical materials or flexible electronic devices.

[0048] Compared with the prior art, this application has the following beneficial effects:

[0049] The viscosity-adjustable hydrogel material provided in this application can easily achieve the compatibility and regulation of the two properties of the hydrogel material surface, sticky and non-sticky, through the selection of chemical components and the regulation of dosage, and at the same time has antifreeze and moisture retention, self-healing properties, biocompatibility and flexibility. This application designs and optimizes the raw materials for preparing the viscosity-adjustable hydrogel, and the viscosity-adjustable hydrogel material can be cut and left to stand for 48 hours to achieve self-healing; the adhesion of the viscosity hydrogel material can be as high as 60N / m; it has good antifreeze properties when frozen at -18℃ for 24 hours, and there is no ice on the surface; the mass reduction rate is as low as 3.8% when left to stand for 7 days at room temperature, and it has good moisture retention. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a photo of the self-healing performance test of the viscosity-adjustable hydrogel material provided in Example 3.

[0051] Figure 2 This is a photo of the self-healing performance test of the hydrogel material provided in Example 1.

[0052] Figure 3 This is a photo of the viscoelastic tensile test of the viscosity-adjustable hydrogel material provided in Example 1.

[0053] Figure 43 is a comparative diagram of the adhesion of the viscosity-adjustable hydrogel materials provided in Example 1 and Example 2.

[0054] Figure 5 This is a bar graph showing the biocompatibility test of the viscosity-adjustable hydrogel material provided in Example 1. DETAILED DESCRIPTION

[0055] The technical solution of the present application is further described below in conjunction with the accompanying drawings and through specific implementation methods. Those skilled in the art should understand that the embodiments are only to help understand the present application and should not be regarded as specific limitations of the present application.

[0056] The sources of some components in the following examples and comparative examples are as follows:

[0057] (1) Polyethylene glycol diacrylate: number average molecular weight 1000, purchased from Aladdin Chemical Reagent;

[0058] (2) Polyethylene oxide: average molecular weight 1,000,000, purchased from BASF Biotechnology Co., Ltd., Hefei.

[0059] Example 1

[0060] A viscosity-adjustable hydrogel material. The raw materials for preparing the viscosity-adjustable hydrogel material include the following components in parts by weight: 20 parts by weight of acrylamide, 1 part by weight of polyethylene glycol diacrylate, 3 parts by weight of polyethylene oxide, 2 parts by weight of dopamine hydrochloride, 50 parts by weight of glycerol, 0.01 parts by weight of lithium magnesium silicate, 50 parts by weight of water and 0.2 parts by weight of 2-hydroxy-2-methyl-1-phenyl-1-propanone.

[0061] A method for preparing a hydrogel material with adjustable viscosity, the preparation method comprising the following steps:

[0062] (1) Mixing the raw materials for preparing the adjustable viscosity hydrogel material provided in this embodiment, acrylamide, polyethylene glycol diacrylate, polyethylene oxide, dopamine hydrochloride, glycerol, lithium magnesium silicate and water, at a mixing temperature of 40° C., and stirring for 24 hours to obtain a hydrogel solution precursor;

[0063] (2) adding 2-hydroxy-2-methyl-1-phenyl-1-propanone to the hydrogel solution precursor obtained in step (1), continuing to stir for more than 10 minutes to obtain a reaction system, and then pouring it into a mold;

[0064] (3) The reaction system obtained in step (2) is reacted under ultraviolet light for 2 minutes to obtain the viscosity-adjustable hydrogel material.

[0065] Example 2

[0066] A viscosity-adjustable hydrogel material. The raw materials for preparing the viscosity-adjustable hydrogel material include the following components in parts by weight: 15 parts by weight of acrylamide, 5 parts by weight of polyethylene glycol diacrylate, 0.5 parts by weight of polyethylene oxide, 0.01 parts by weight of dopamine hydrochloride, 50 parts by weight of glycerol, 0.1 parts by weight of lithium magnesium silicate, 50 parts by weight of water and 0.2 parts by weight of 2-hydroxy-2-methyl-1-phenyl-1-propanone.

[0067] A method for preparing a hydrogel material with adjustable viscosity, which differs from Example 1 only in that the raw materials for preparation in step (1) are the raw materials for preparation provided in this example, and the remaining process parameters and steps are the same as those in Example 1.

[0068] Example 3

[0069] A viscosity-adjustable hydrogel material. The raw materials for preparing the viscosity-adjustable hydrogel material include the following components in parts by weight: 25 parts by weight of acrylamide, 1 part by weight of polyethylene glycol diacrylate, 3 parts by weight of polyethylene oxide, 1 part by weight of dopamine hydrochloride, 50 parts by weight of glycerol, 0.01 part by weight of lithium magnesium silicate, 50 parts by weight of water and 0.2 part by weight of 2-hydroxy-2-methyl-1-phenyl-1-propanone.

[0070] A method for preparing a hydrogel material with adjustable viscosity, which differs from Example 1 only in that the raw materials for preparation in step (1) are the raw materials for preparation provided in this example, and the remaining process parameters and steps are the same as those in Example 1.

[0071] Example 4

[0072] A viscosity-adjustable hydrogel material. The raw materials for preparing the viscosity-adjustable hydrogel material include the following components in parts by weight: 30 parts by weight of acrylamide, 1 part by weight of polyethylene glycol diacrylate, 1 part by weight of polyethylene oxide, 0.01 part by weight of dopamine hydrochloride, 50 parts by weight of glycerol, 0.1 part by weight of lithium magnesium silicate, 50 parts by weight of water and 0.2 part by weight of 2-hydroxy-2-methyl-1-phenyl-1-propanone.

[0073] A method for preparing a hydrogel material with adjustable viscosity, which differs from Example 1 only in that the raw materials for preparation in step (1) are the raw materials for preparation provided in this example, and the remaining process parameters and steps are the same as those in Example 1.

[0074] Comparative Example 1

[0075] A hydrogel material, which is different from Example 3 only in that the raw materials for preparing the hydrogel material do not contain 1 part by weight of dopamine hydrochloride, and the other raw materials are the same as those in Example 3.

[0076] A method for preparing a hydrogel material, which differs from Example 3 only in that the raw materials for preparation in step (1) are the raw materials for preparation provided in this comparative example, and the remaining process parameters and steps are the same as those in Example 3.

[0077] Comparative Example 2

[0078] A hydrogel material, which is different from Example 1 only in that glycerin is not added to the raw materials for preparing the hydrogel material, the added amount of water is 100 parts by weight, and the other raw materials are the same as those in Example 1.

[0079] A method for preparing a hydrogel material, which differs from Example 1 only in that the raw materials for preparation in step (1) are the raw materials for preparation provided in this comparative example, and the remaining process parameters and steps are the same as those in Example 1.

[0080] Performance Testing

[0081] (1) Self-healing performance test: The hydrogel was cut and then spliced. After standing for 48 hours, it was stretched to more than 300% without breaking.

[0082] (2) Biocompatibility test: The MTT method was used to evaluate the cytotoxicity of the material to NIH3T3 cells. The test was performed at 24 h, 72 h, and 120 h during the cell culture process. If the cell survival rate (relative stability) was ≥ 85%, it could be proved that the hydrogel material was biocompatible.

[0083] (3) Adhesion test: Using the peeling test method, a PET film or fiber cloth is attached to the surface of a 5×1.5×0.1 cm hydrogel and then peeled off with a certain force. The greater the peeling force, the stronger the adhesion of the hydrogel sample.

[0084] (4) Viscoelastic tensile test: Two hydrogel sections of 3×2×0.2 cm in size were partially overlapped with each other to a length of 1 to 2 cm. The two ends were then fixed and stretched. The length of the hydrogel at the maximum tensile deformation was measured to obtain the maximum tensile length increment.

[0085] (5) Freeze resistance test: A hydrogel sample of 4×4 cm and 1 mm thick was placed in a refrigerator and frozen at -18°C for 24 h. After taking it out, observe whether there is ice on the surface.

[0086] (6) Moisture retention test: A hydrogel sample with a diameter of 13 cm and a thickness of 4 cm and a certain mass was left standing at room temperature for 7 days and then tested for quality.

[0087] The various properties of the hydrogel materials obtained in Examples 1 to 4 and Comparative Examples 1 to 2 were tested according to the above performance testing method. The test results are as follows: Figures 1 to 4 , as shown in Table 1.

[0088] Table 1

[0089]

[0090] Figure 1 This is a photo of the self-healing performance test of the hydrogel material provided in Example 3; Figure 1 It can be seen that the hydrogel material provided in Example 3 can achieve self-healing after being cut, and can still maintain good flexibility after self-healing. Figure 2 This is a photo of the self-healing performance test of the hydrogel material provided in Example 1; Figure 2 It can be seen that the hydrogel material provided in Comparative Example 1 has no self-healing property because dopamine hydrochloride is not added. Figure 3 The viscoelastic tensile test photo of the viscosity-adjustable hydrogel material provided in Example 1; Figure 3 It can be seen that the hydrogel material provided in Example 1 has good viscoelastic stretchability, and the stretched length can reach 800% of the original length. Figure 4 A comparative diagram of the adhesion of the adjustable viscosity hydrogel material provided in Example 1 and Example 2; Figure 4 It can be seen that the viscosity-adjustable hydrogel material provided in the present application can achieve the regulation of the viscosity and non-stickiness of the hydrogel material by regulating the amount of raw materials used in its preparation. Figure 5 The biocompatibility test bar graph of the viscosity adjustable hydrogel material provided in Example 1; Figure 5 It can be seen that the viscosity-adjustable hydrogel material provided in Example 1 still has a relative stability of up to 95% even after 120 hours, indicating that the hydrogel material provided in this embodiment has good biocompatibility. It can be seen from Table 1 that the viscosity-adjustable hydrogel material provided in this application has good antifreeze properties. When the moisture retention test is performed, the mass reduction rate of the viscosity-adjustable hydrogel material provided in this application is 3.8%, which is lower than 76.4% of Comparative Example 2, indicating that the viscosity-adjustable hydrogel material provided in this application has good moisture retention.

[0091] The applicant declares that the present application uses the above-mentioned embodiments to illustrate the detailed process flow of the present application, but the present application is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present application must rely on the above-mentioned detailed process flow to be implemented. The technicians in the relevant technical field should understand that any improvement to the present application, the equivalent replacement of the raw materials of the present application product, the addition of auxiliary components, the selection of specific methods, etc., all fall within the scope of protection and disclosure of the present application.

Claims

1. A viscosity adjustable hydrogel material, wherein the raw materials for its preparation include the following components in parts by weight: 10 to 30 parts by weight of monomer, 1 to 20 parts by weight of cross-linking agent, 0.1 to 5 parts by weight of long-chain polymer, 0.01 to 5 parts by weight of dopamine hydrochloride, 0.01 to 5 parts by weight of clay and 50 to 90 parts by weight of water.

2. The viscosity-adjustable hydrogel material according to claim 1, wherein: The monomer includes any one of acrylamide, methacrylamide or hydroxyethyl methacrylate or a combination of at least two thereof.

3. The viscosity-adjustable hydrogel material according to claim 1, wherein: The cross-linking agent includes polyethylene glycol diacrylate and / or N,N'-methylenebisacrylamide; the number average molecular weight of the polyethylene glycol diacrylate is 600-1000.

4. The viscosity-adjustable hydrogel material according to claim 1, wherein: The long-chain polymer includes polyethylene oxide and / or hydroxyethyl cellulose; the average molecular weight of the polyethylene oxide is 100,000 to 8,000,000; and the viscosity of the hydroxyethyl cellulose is 100 to 6,400 mPa.s.

5. The viscosity-adjustable hydrogel material according to claim 1, wherein: The clay comprises any one of lithium magnesium silicate, carbon fiber, silver nanoparticles, silicon dioxide nanoparticles or graphene oxide, or a combination of at least two thereof; the particle size of the silver nanoparticles is 10 to 100 nm; the particle size of the silicon dioxide nanoparticles is 10 to 500 nm.

6. The viscosity-adjustable hydrogel material according to any one of claims 1 to 5, wherein: The raw materials for preparing the adjustable viscosity hydrogel material further include 10 to 50 parts by weight of a moisturizer; the moisturizer includes a polyol; and the polyol includes glycerol and / or ethylene glycol.

7. The viscosity-adjustable hydrogel material according to any one of claims 1 to 5, wherein: The raw materials for preparing the adjustable viscosity hydrogel material also include 0.2 to 2 parts by weight of an initiator; the initiator includes any one of a photoinitiator or a thermal initiator, and a photoinitiator is further preferred; the photoinitiator includes 2-hydroxy-2-methyl-1-phenyl-1-propanone and / or 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide.

8. A method for preparing the viscosity-adjustable hydrogel material according to any one of claims 1 to 7, comprising the following steps: The monomer, the cross-linking agent, the long-chain polymer, the dopamine hydrochloride, the clay and the water are mixed to obtain the hydrogel solution precursor; the hydrogel solution precursor is reacted in the presence of the initiator to obtain the viscosity-adjustable hydrogel material.

9. The preparation method according to claim 8, wherein: The mixed material also includes a moisturizer; the mixing temperature is 25 to 60° C.; the initiator is a photoinitiator, and the reaction is carried out under ultraviolet light; and the reaction time is 1 to 5 minutes.

10. Use of the viscosity-adjustable hydrogel material according to any one of claims 1 to 7 in biomedical materials or flexible electronic devices.

Citation Information

Patent Citations

  • High-extension, high-adhesion and high-self-healing double network hydrogel and preparation method and application thereof

    CN110240712A

  • Ultraviolet curing medical hydrogel and preparation method thereof

    CN115286731A

  • Nanometer clay-containing high absorptive hydrogel as well as preparation method and application thereof

    CN101942167A

  • Preparation method of self-adhesive hydrogel having anti-freezing / heat-resistant performance

    CN107641179A

  • Preparation method of self-repairing bionic hydrogel with toughness and adhesion

    CN112442193A